ANALISIS FAKTOR-FAKTOR KEBERHASILAN PEMBELAJARAN MENULIS PUISI DI SMA NEGERI PURWOKERTO - Wilasinta, Tisa Agistia; Memet Sudaryanto; Nur Indah Solikhati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to identify the factors that influence the success of poetry-writing instruction among students in public senior high schools in Purwokerto using a quantitative approach with Exploratory Factor Analysis (EFA). A total of 674 students from five public senior high schools were selected through cluster sampling. The research instrument consisted of a 39-item Likert-scale questionnaire that had undergone content validation using Aiken’s V and reliability testing with Cronbach’s Alpha (0.948). The KMO value (0.944) and Bartlett’s Test of Sphericity confirmed that the data were suitable for factor analysis. The EFA results revealed seven principal factors explaining 62.4% of the total variance, which include dominant dimensions related to students’ psychological readiness, learning engagement, learning experiences, teacher support, classroom climate, and other external supporting factors. These findings indicate that the success of poetry writing instruction is multidimensional and shaped by the interplay of internal motivation, pedagogical strategies, and a supportive learning environment. The results are expected to serve as a foundation for developing more effective, creative, and contextually relevant poetry-learning strategies aligned with students’ needs.